Discovering Trends of Agricultural Drought in Tihama Plain, Yemen : A Preliminary Assessment - Noorazuan Md hashim; Ali Ahmed Dhaif Allah; azahan Awang (Faculty of Geography, Universitas Gadjah Mada, 2017)
Agricultural drought is characterized by lack of sufficient moisture in the surface soil layers to support crop and forage growth. Indicators of agricultural drought often are precipitation, temperature and soil moisture to measure soil moisture and crop yield. This study aims to assess spatiotemporal of drought in the Tihama Plain, which is one of the most important agricultural areas in Yemen, where contributes about 42% of the total agricultural production in the country. In recent years, the Tihama Plain faced changes in the rainy season, which reflect negatively on agriculture production and water security in the area. In this study the Standardized Precipitation Index (SPI) was used to temporal evaluation of the situation of drought, also it has been used Geographic Information Systems (GIS) in order to show the spatial variability distribution of drought in the study area. The analysis results by SPI-6 showed that the years 1984,1991,2002, 2003,2004,2005,2006 and 2008 were the most affected by drought during the study period 30 years (1980-2010), also show that the year 1991 was the worst years of drought experienced by the study area. Based on the fact that the study area is the most important agricultural areas in Yemen, it is recommended a study the drought and its impact on agricultural crops in the area.